2019
DOI: 10.2174/1871520619666190118120030
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diarrheal Drug Repositioning in Tumour Cell Cytotoxicity

Abstract: Background: Drug repositioning is becoming an ideal strategy to select new anticancer drugs. In particular, drugs treating the side effects of chemotherapy are the best candidates. Objective: In this present work, we undertook the evaluation of anti-tumour activity of two anti-diarrheal drugs (nifuroxazide and rifaximin). Methods: Anti-proliferative effect against breast cancer cells (MDA-MB-231, MCF-7 and T47D) was assessed by MTT analysis, the Brdu incorporation, mitochondrial permeability and caspase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although 22 molecules inhibited the [S¡R] transition at 1 M, microscopic analysis of the phenotype indicated that some of them were parasiticidal (and, thus, unlikely to have any direct effect on the egress/invasion process). Molecules inhibiting the [S¡R] transition only at 3 M and 10 M were not considered for further experiments since at higher concentrations the observed inhibition could have been due to general cytotoxicity on merozoite viability (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…Although 22 molecules inhibited the [S¡R] transition at 1 M, microscopic analysis of the phenotype indicated that some of them were parasiticidal (and, thus, unlikely to have any direct effect on the egress/invasion process). Molecules inhibiting the [S¡R] transition only at 3 M and 10 M were not considered for further experiments since at higher concentrations the observed inhibition could have been due to general cytotoxicity on merozoite viability (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…In these activities, the blocking of the STAT3 pathways plays an important role. Nifuroxazide can be effective as prophylaxis or second-line therapy for aGvHD (4)(5)(6)(7)(8)(28)(29)(30). It can be assumed that this old drug will find a new application in medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Although 29 molecules inhibited [S→R] transition at 1 µM, microscopic analysis of phenotype indicated that some of them were parasiticidal (and thus unlikely to have any direct effect on the egress/invasion process). Molecules inhibiting [S→R] transition only at 3 µM and 10 µM were not consider for further study since at higher concentrations the observed inhibition can be due to general cytotoxicity on merozoite viability 4344 .…”
Section: Resultsmentioning
confidence: 99%